Numerical simulation of unsteady dense granular flows with rotating geometries - Bennani, L.; Neau, H.; Baudry, C.; Laviéville, J.; Fede, P.; Simonin, O. (Chemical engineering research & design, 2017)
•A rotating mesh method for the simulation of unsteady dense granular flows is presented.•Numerical validation by comparison to conventional methods (rotating frame, sliding wall) shows excellent agreement.•The method is successfully applied to the simulation of a complex large scale stirrer. In chemical engineering applications, it is not uncommon to encounter reactors featuring rotating parts. As these rotating parts are present in order to enhance processes such as chemical reactions and/or ensure homogeneity, it is essential to take them into account to perform predictive numerical simulations. This aspect can be particularly challenging, even more so when complex industrial geometries are to be treated. In this paper a numerical methodology for simulating unsteady granular flow in rotating geometries is presented. The method is based on splitting the domain into static and rotating parts. The information between rotating and static parts is passed by a non-conformal mesh matching technique. The presented methodology is validated numerically by comparing its results with other conventional methods. The method is then applied to an industrial scale problem. The applicability of the method and the way it may be used to investigate complex flow is demonstrated. Therefore this approach enables to consider the full geometry of complex reactors. It opens the door to further investigation, optimization and design of industrial scale chemical processes.